ADCY5 mutations are another cause of benign hereditary chorea. (7th July 2015) - Mencacci, Niccolo E.; Erro, Roberto; Wiethoff, Sarah; Hersheson, Joshua; Ryten, Mina; Balint, Bettina; Ganos, Christos; Stamelou, Maria; Quinn, Niall; Houlden, Henry; Wood, Nicholas W.; Bhatia, Kailash P.
Abstract : Objective: To determine the contribution of ADCY5 mutations in cases with genetically undefined benign hereditary chorea (BHC). Methods: We studied 18 unrelated cases with BHC (7 familial, 11 sporadic) who were negative for NKX2-1 mutations. The diagnosis of BHC was based on the presence of a childhood-onset movement disorder, predominantly characterized by chorea and no other major neurologic features. ADCY5 analysis was performed by whole-exome sequencing or Sanger sequencing. ADCY5 and NKX2-1 expression during brain development and in the adult human brain was assessed using microarray analysis of postmortem brain tissue. Results: The c.1252C>T; p.R418W mutation was identified in 2 cases (1 familial, 1 sporadic). The familial case inherited the mutation from the affected father, who had a much milder presentation, likely due to low-grade somatic mosaicism. The mutation was de novo in the sporadic case. The clinical presentation of these cases featured nonparoxysmal generalized chorea, as well as dystonia in the most severely affected, but no facial myokymia. We observed significant progression of symptoms in ADCY5 mutation carriers, in contrast to BHC secondary to NKX2-1 mutations. The difference in the clinical course is mirrored by the brain expression data, showing increasing ADCY5 expression in the striatum during brain development, whereas NKX2-1 shows an opposite trend. Conclusions: Our study identifies mutations in ADCY5, the gene previously linked to familial dyskinesia with facial myokymia, as a cause of familial and sporadic BHC. ADCY5 genetic analysis should be performed in cases with a benign choreiform movement disorder even in the absence of facial myokymia.